2013
DOI: 10.1021/ja408547g
|View full text |Cite
|
Sign up to set email alerts
|

Linear versus Dendritic Molecular Binders for Hydrogel Network Formation with Clay Nanosheets: Studies with ABA Triblock Copolyethers Carrying Guanidinium Ion Pendants

Abstract: ABA-triblock copolyethers 1a-1c as linear polymeric binders, in combination with clay nanosheets (CNSs), afford high-water-content moldable supramolecular hydrogels with excellent mechanical properties by constructing a well-developed crosslinked network in water. The linear binders carry in their terminal A blocks guanidinium ion (Gu(+)) pendants for adhesion to the CNS surface, while their central B block comprises poly(ethylene oxide) (PEO) that serves as a flexible linker for adhered CNSs. Although previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(116 citation statements)
references
References 54 publications
3
111
0
Order By: Relevance
“…, noncovalent manipulation of enzymes. Recently, we confirmed that non-dendritic, linear polymers bearing side-chain Gu + pendants 17 are readily accessible alternatives to our prototype dendritic molecular glues. Hence, in the present study, we designed linear Glue n –BA with short ( n = 10) and long ( n = 29) glue moieties (Fig.…”
Section: Introductionsupporting
confidence: 68%
“…, noncovalent manipulation of enzymes. Recently, we confirmed that non-dendritic, linear polymers bearing side-chain Gu + pendants 17 are readily accessible alternatives to our prototype dendritic molecular glues. Hence, in the present study, we designed linear Glue n –BA with short ( n = 10) and long ( n = 29) glue moieties (Fig.…”
Section: Introductionsupporting
confidence: 68%
“…Addition of CB [8] to a colorless solution of the two copolymers leads to transformation into a highly viscous, colored supramolecular hydrogel with a cross-linking density that can be controlled by the amount of CB [8]. The hydrogels exhibit solidlike mechanical properties at 5 wt% in water, with plateau moduli of 350-600 Pa at a cross-linking density in the range of 2.5-10 %, which is complementary to other supramolecular hydrogels that exhibit higher mechanical strength [236,237]. In a following work, Sherman and coworkers reported on ultrahigh water content hydrogels (up to 99.75 % of water) based on the same host-guest complexation but derived from renewable cellulose derivatives [238,239].…”
Section: Macrocyclic Inclusion Complexationmentioning
confidence: 98%
“…The hydrogels exhibit an exceptional mechanical strength (G 0 up to 10 6 Pa) as well as rapid self-healing. In a follow-up study, the same group was able to prepare similar hydrogels by using linear ABA triblock copolyethers carrying guanidinium groups in their end blocks [237]. These hydrogels are as tough as the dendrimer-based gels, but the linear binders can be obtained by much less elaborate syntheses from starting materials that are readily available.…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…Based on such methodology, well-designed linear macromolecules with proper surface functional groups can also crosslink with CNPs through a salt-bridge to form nanocomposite hydrogels. For example, Tamesue et al 79 mixed a linear macromolecule with LAPONITE s XLG NPs, which were pre-dispersed in water with a minute amount of sodium polyacrylate. In this way, a supramolecular nanocomposite hydrogel composed of linear macromolecule and LAPONITE s XLG NPs was successfully obtained.…”
Section: Supramolecular Assemblymentioning
confidence: 99%